Intensity-modulated radiation therapy for early-stage breast cancer: is it ready for prime time? - Chan TY (Dove Medical Press, 2017)
Tabitha Y Chan, Poh Wee Tan, Johann I Tang Department of Radiation Oncology, National University Cancer Institute, Singapore, Singapore Abstract: Whole breast external beam radiotherapy (WBEBRT) is commonly used as an essential arm in the treatment management of women with early-stage breast cancer. Dosimetry planning for conventional WBEBRT typically involves a pair of tangential fields. Advancement in radiation technology and techniques has the potential to improve treatment outcomes with clinically meaningful long-term benefits. However, this advancement must be balanced with safety and improved efficacy. Intensity-modulated radiation therapy (IMRT) is an advanced technique that shows promise in improving the planning process and radiation delivery. Early data on utilizing IMRT for WBEBRT demonstrate more homogenous dose distribution with reduction in organs at risk doses. This translates to toxicities reduction. The two common descriptors for IMRT are forward-planning “fields in field” and inverse planning. Unlike IMRT for other organs, the aim of IMRT for breast planning is to achieve dose homogeneity and not organ conformality. The aim of this paper was to evaluate whether IMRT is ready for prime time based on these three points: 1) workload impact, 2) the clinical impact on the patient’s quality of life, and 3) the appropriateness and applicability to clinical practice. Keywords: early-stage breast cancer, radiotherapy, intensity-modulated radiation therapy, workload impact, quality of life, clinical practice